P059 Ex vivo comparison of baricitinib, upadacitinib, filgotinib and tofacitinib for cytokine signalling in human leukocyte subpopulations. (21st February 2018) - McInnes, IB; Higgs, R; Lee, J; Macias, WL; Na, S; Ortmann, RA; Rocha, G; Wehrman, T; Zhang, X; Zuckerman, SH; Taylor, PC; Perrier, C
Abstract : Introduction: Baricitinib (BARI), an oral selective Janus kinase (JAK) 1/2 inhibitor, approved in the EU for moderate to severe active RA. Objectives: To compare in vitro cellular pharmacology of BARI to upadacitinib (ABT), filgotinib (FILGO), and tofacitinib (TOFA), three JAK inhibitors (JAKis) currently approved or in clinical development. Methods: Peripheral blood mononuclear cells from healthy donors (n=6–12) were incubated with different JAKis. After cytokine stimulation, phosphorylated signal transducer and activator of transcription (pSTAT) levels were measured and IC50 calculated in phenotypically gated leukocyte subpopulations. Therapeutic dose relevance of in vitro analysis was assessed using calculated mean concentration-time (CT) profiles over 24 hour JAKi-treated subjects (BARI 4 mg QD; ABT 15 and 30 mg QD; FILGO 100 and 200 mg QD; TOFA 5 and 10 mg BID). Time above IC50 (T>IC; h/day) and average daily% inhibition of pSTAT formation (%SI) were calculated for each JAKi, cytokine, and cell type. Results: Tested cytokines did not signal in all cell types. When signalling was detected, IC50, %SI, and T>IC for a particular JAKi exhibited similar dose dependent inhibition across cell types. For JAK1/3 dependent signalling across 4 cytokines (IL-2, 4, 15, 21), IC50 for ABT and TOFA were more potent than BARI; FILGO was the least potent. Overlaid on CT profiles, this indicated generally higher%SI and longer T>IC for ABT and TOFA compared to BARI and FILGO. For IL-6 (JAK1/2), %SI and T>IC was TOFA>BARI/ABT>FILGO and for IL-10 (JAK1/TYK2), %SI was TOFA>BARI/ABT>FILGO. IFN-γ (JAK1/2) was modulated only by BARI, ABT, and TOFA. IFN-α (JAK1/TYK2) signalling was most potently inhibited by BARI and ABT. FILGO did not appear to modulate GM-CSF signalling (JAK2/2), while%SI and T>IC were similar between BARI and ABT. Conclusions: JAKis modulate distinct cytokine pathways to differing degrees and durations over 24 hour. BARI and FILGO inhibited JAK1/3 signalling less than ABT and TOFA. No JAKis agent potently or continuously inhibited an individual cytokine signalling pathway throughout dosing interval, implying the varying efficacy and safety profiles of JAKis across disease states. Acknowledgements: Study support: Eli Lilly and Company and Incyte Corporation. Encore of ACR/ARHP-2017 Annual Scientific Meeting, Nov 4–8, 2016; San Diego, CA, USA. Disclosure of interest: None declared